THE RELATIONSHIP MARKETING APPLICATION IN SMALL AND MEDIUM-SIZED ENTERPRISES - SABOU FELICIA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2016)
The paper presents the importance of relationship marketing, the communication between customers and romanian small and medium-sized enterprises, analyzing also how are investigated and resolved the complaints received from the customers. In the paper, I made a study through I analyzed if the small and medium-sized enterprises undertake investigations about the reasons which they have lost customers. The study was conducted during january - february 2016, the main research methods used in the study were observation, documentation, analysis and market survey. Also, I chose the study questionnaire as research tool. From this study resulted that 79,31% of companies surveyed, were concerned and investigated the reasons they lost customers. Customer satisfaction is very important to business success, so it is recommended that companies must pay attention to the customers reactions and customers dissatisfaction consequences.